2018
DOI: 10.1096/fj.201701450rr
|View full text |Cite
|
Sign up to set email alerts
|

RNF4 regulates zebrafish granulopoiesis through the DNMT1‐C/EBPα axis

Abstract: RING finger protein 4 (RNF4) is a multifunctional small ubiquitin-related modifier (SUMO)-targeted ubiquitin E3 ligase (STUbL) ubiquitously expressed in all tissues, and which mainly participates in DNA repair and in chromatin and transcriptional regulation. Although RNF4 has been implicated in hematopoietic disorders, its ontogenic role during hematopoietic development remains undiscovered. We generated a zebrafish rnf4 knockout line by using transcription activator-like effector nucleases technology to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Wang and colleagues recently reported a role of RNF4 in the regulation of zebrafish granulopoiesis through the DNMT1‐C/EBPa axis . In that study, the authors found DNMT1 as a potential new substrate of RNF4.…”
Section: Rnf4 In Developmentmentioning
confidence: 92%
“…Wang and colleagues recently reported a role of RNF4 in the regulation of zebrafish granulopoiesis through the DNMT1‐C/EBPa axis . In that study, the authors found DNMT1 as a potential new substrate of RNF4.…”
Section: Rnf4 In Developmentmentioning
confidence: 92%
“…The neutrophils were largely decreased in rnf4-deficient zebrafish larvae during both primitive and definitive myelopoiesis. Mechanistically, the hypermethylation of c/ebpα promoter by SUMOylated DNA methyltransferase 1 (DNMT1) led to granulopoiesis defect in rnf4-deficient zebrafish (Wang et al 2018a ). Besides DNMT1, another methyltransferase, smyd5, suppresses the excessive expressions of primitive and definitive myelopoietic genes, such as pu.1 , mpx , l-plastin , and c-myb (Fujii et al 2016 ).…”
Section: Using Zebrafish To Explore the Regulation Of Myelopoiesismentioning
confidence: 99%
“…One gene of interest is the small ubiquitin-related modifier (SUMO)-targeted E3 ligase, RNF4. RNF4 is primarily involved in DNA damage repair and chromatin regulation, contributing significantly to maintaining genomic integrity and the loss of rnf4 results in defects in embryonic myeloid development in zebrafish [72]. RNF4 regulates granulopoiesis via the regulation of DNA methyltransferase 1 (DNMT1) and the CCAAT/enhancer-binding protein α (C/EBPα) axis.…”
Section: Hematopoiesismentioning
confidence: 99%